A single-center study of two types of upper kidney preservation surgery for complete duplicated kidney in children - Chu, Han; Zhang, Xian-sheng; Cao, Yong-sheng; Deng, Qi-fei (Frontiers in Pediatrics, 2022)
Objective: To compare the efficacy, advantages, and disadvantages of insertable ureteral reimplantation (UC group) and ureteral end-to-side anastomosis (UU group) in the treatment of duplicate kidney, and summarize the clinical experience in diagnosis and treatment. Methods: Retrospective analysis was performed on 20 cases of duplicate kidney in our hospital from April 2016 to June 2021, including 11 cases of insertable ureteral reimplantation and 9 cases of end-to-side ureteral anastomosis. There were 8 boys, 12 girls, 12 left and 8 right. There were 3 cases of urinary tract infection and 9 cases of urinary incontinence, all of the rest were found by B ultrasound in physical examination. The median age was 33.5 months. Preoperative and postoperative renal pelvis separation, ureteral dilation, operation time, and drainage tube indwelling time were compared. Results: Statistical differences existed between the two groups in terms of operative time (P=0.03), degree of pre-operative and post-operative hydronephrosis (UC:P=0.00, UU:P=0.02), degree of ureteral dilatation (UC :P=0.00, UU:P=0.001), drainage time (P=0.02) and length of hospital stay (P=0.007). There was no statistical difference in the degree of preoperative and postoperative hydronephrosis and ureteral dilatation (preoperative P=0.88, P=0.21, postoperative P=0.375, P=0.92) compared between the two groups. Conclusion: The two methods have their advantages and disadvantages, both can be used as the choice of renal sparing therapy for the complete duplicate kidney, it is necessary to choose the appropriate method according to the situation of children and the surgical experience of the doctors. Double J tube or ureter stent placement is helpful for finding and protecting ureter intraoperative, without increasing the difficulty in operation, and can prevent anastomosis or ureteral orifice stenosis.